MELTING ENTHALPIES OF MANTLE PERIDOTITE: CALORIMETRIC DETERMINATIONS IN THE SYSTEM CAO-MGO-AL2O3-SIO2 AND APPLICATION TO MAGMA GENERATION - Kojitani H.; Akaogi M. (My University, 1997)
High-temperature drop calorimetry in the temperature range of 1398-1785 K was performed for the samples of mixtures of synthetic anorthite (An), diopside (Di), enstatite (En) and forsterite (Fo) with the same compositions as those of primary melts generated at 1.1, 3 and 4 GPa at most 10° above the solidus of anhydrous mantle peridotite in the CaO-MgO-Al2O3-SiO2 system. From the differences between the heat contents (HT - H298) of liquid and that of crystal mixture at the liquidus temperature, melting enthalpies of the samples of 1.1, 3 and 4 GPa-primary melt compositions were determined at 1 atm to be 531 +/- 39 J . g-1 at 1583 K, 604 +/- 21 J . g-1 at 1703 K, 646 +/- 21 J . g-1 at 1753 K, respectively. These heat of fusion values suggest that mixing enthalpy of the melt in the An-Di-En-Fo system is approximately zero within the experimental errors when we use the heat of fusion of Fo by Richet et al. (P. Richet, F. Leclerc, L. Benoist, Melting of forsterite and spinel, with implications for the glass transition of Mg2SiO4 liquid, Geophys. Res. Lett. 20 (1993) 1675-1678). The measured enthalpies of melting at 1 atm were converted into those for melting reactions which occur under high pressures by correcting enthalpy changes associated with solid-state mineral reactions. Correcting the effects of pressure, temperature and FeO and Na2O components on the melting enthalpies at 1 atm, heat of fusion values of a representative mantle peridotite just above the solidus under high pressure were estimated to be 590 J at 1.1 GPa and 1523 K, 692 J at 3 GPa and 1773 K, and 807 J at 4 GPa and 1923 K for melting reactions producing liquid of 1 g, with uncertainties of 50 J. By applying these melting enthalpies to a mantle diapir model which generates present MORBs, a potential mantle temperature of 1533 K has been estimated, assuming an eruption temperature of magma of 1473 K.
Keywords: MELTING; ENTHALPY; MANTLE; PERIDOTITE; HIGH-TEMPERATURE; CALORIMETRY; MELTS; MANTLE PLUMES